2020
DOI: 10.1042/bcj20200452
|View full text |Cite
|
Sign up to set email alerts
|

NRF2/ACSS2 axis mediates the metabolic effect of alcohol drinking on esophageal squamous cell carcinoma

Abstract: Alcohol drinking is a leading risk factor for the development of esophageal squamous cell carcinoma (ESCC). However, the molecular mechanisms of alcohol-associated ESCC remain poorly understood. One of the most commonly mutated genes in ESCC is nuclear factor erythroid 2 like 2 (NFE2L2 or NRF2), which is a critical transcription factor regulating oxidative stress response and drug detoxification. When NRF2 is hyperactive in cancer cells, however, it leads to metabolic reprogramming, cell proliferation, chemora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Ethanol has been shown to enhance the expression and nuclear localization of 5‐lipoxygenase and stimulate the biosynthesis of pro‐inflammatory leukotriene B4 in oral cancer cells [48]. Ethanol‐derived acetate may also feed into energy metabolism as a carbon source [49], or promote histone acetylation and thus regulate gene transcription [50]. Ethanol exposure increases the mutation rate through error‐prone polymerases [51].…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol has been shown to enhance the expression and nuclear localization of 5‐lipoxygenase and stimulate the biosynthesis of pro‐inflammatory leukotriene B4 in oral cancer cells [48]. Ethanol‐derived acetate may also feed into energy metabolism as a carbon source [49], or promote histone acetylation and thus regulate gene transcription [50]. Ethanol exposure increases the mutation rate through error‐prone polymerases [51].…”
Section: Discussionmentioning
confidence: 99%
“…In esophageal cancer cells and the mouse esophagus, knockout of either NRF2 or ACSS2 reduced ACSS2 expression, which subsequently decreased acetyl-CoA and ATP levels. Moreover, lipid synthesis in esophageal carcinoma cells was decreased, and the invasion ability of these cells was weakened [95].…”
Section: Gastrointestinal Cancermentioning
confidence: 99%
“…Milada et al found that FA spectra changed in plasma phosphatidylcholine in esophageal squamous cell carcinoma patients, which might be correlated with abnormal fatty acid metabolism in cancer (e.g., altered de novo fatty acid synthesis, β -oxidation, desaturation, and extension). The above changes may be correlated with the prominent functioning of neoadjuvant chemotherapy [ 23 ].…”
Section: Introduction To Esophageal Cancermentioning
confidence: 99%
“…The NRF2/ACSS2 axis will allow ESCC cells to exploit ethanol-derived acetate as their energy source. It can regulate downstream ethanol metabolism and metabolic reprogramming in ESCC, while inducing lipid synthesis and alcohol-related ESCC [ 23 ].…”
Section: Introduction To Esophageal Cancermentioning
confidence: 99%
See 1 more Smart Citation